2022
DOI: 10.2147/ppa.s354686
|View full text |Cite
|
Sign up to set email alerts
|

Key Factors Relevant for Healthcare Decisions of Patients with Type 1 and Type 2 Diabetes in Secondary Care According to Healthcare Professionals

Abstract: Understanding which factors are important for healthcare decisions of patients with diabetes in clinical practice is important to personalise diabetes care strategies and tailor care plans to the individual. The main drivers for these healthcare decisions remain unclear. This study assessed which key factors are relevant for healthcare decisions during clinical consultations for patients with type 1 diabetes (T1DM) and type 2 diabetes (T2DM), according to healthcare professionals. Materials and Methods: Annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A study by Ruissen et al found that healthcare providers also recognize the importance of discussing person-related factors in the diabetes treatment decision-making process. 29 Patient’s preferences and quality of life were reported as key factors relevant for diabetes treatment decisions according to secondary care healthcare providers. Therefore, not only the biological effects of a treatment needs to be discussed (which is standard) during the decision-making process, but also the impact of a treatment on a patient’s quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ruissen et al found that healthcare providers also recognize the importance of discussing person-related factors in the diabetes treatment decision-making process. 29 Patient’s preferences and quality of life were reported as key factors relevant for diabetes treatment decisions according to secondary care healthcare providers. Therefore, not only the biological effects of a treatment needs to be discussed (which is standard) during the decision-making process, but also the impact of a treatment on a patient’s quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…We can't process all available information perfectly, and so we often rely on heuristics (mental shortcuts) or satisfice (make reasonable choices based on limited information) instead of aiming for the absolute optimal choice. In healthcare, this might explain why patients might choose a convenient (but potentially less effective) treatment option over a more complex but potentially more beneficial one (Ruissen et al, 2022). • Psychological Biases: BE highlights how systematic biases in our thinking can influence healthcare decisions.…”
Section: Unveiling the Labyrinth Of Healthcare Choices: A Psychoecono...mentioning
confidence: 99%
“… 28 As such, Leiden University Medical Center (LUMC), a university teaching hospital in the Netherlands, has adopted a structured consultation model in diabetes care. 29 This model focuses on both patients’ life- and health-related factors, e.g., social context, which may involve financial hardship. It is standard practice to consider travel time and out-of-pocket costs in the patient-clinician interaction, especially since LUMC is a referral center for patients with rare types of diabetes, e.g., monogenic diabetes mellitus.…”
Section: Shared Decision-making Between Patient and Clinician: Discus...mentioning
confidence: 99%